Managerial Networks and Exploration in a Professional Service Firm. Issue 2 (February 2017) - Rogan, Michelle; Mors, Marie Louise
A firm's growth and survival depends on the ability of its managers to explore for new business and knowledge; yet, exploration is challenging for most large, established firms. Extending prior research into networks and exploration, we propose that a key characteristic of managers' external networks – the extent to which their networks include relationships built using predominately individual rather than firm resources – is positively related to managers' abilities to explore for new business and knowledge in large firms. We propose that networks with more individual ties provide more diverse knowledge, enable greater autonomy and ease access to resources from contacts, hence facilitating exploration. Analysis of an original dataset of external networks of 77 senior managers in a large global consulting firm provides support for our arguments. We find that individual ties are positively related to exploration and, furthermore, that the positive (negative) relationship between sparse (dense) networks and exploration increases with the number of individual ties in managers' networks.